Does vitamin D supplementation alter plasma adipokines concentrations? A systematic review and meta-analysis of randomized controlled trials. - Dinca, Madalina (2016)
We aimed to elucidate the role of vitamin D supplementation on adipokines through a systematic review and a meta-analysis of randomized placebo-controlled trials (RCTs). The search included PUBMED, Scopus, Web of Science and Google Scholar through July 1st, 2015. Finally we identified 9 RCTs and 484 participants. Meta-analysis of data from 7 studies did not find a significant change in plasma adiponectin concentrations following vitamin D supplementation (mean difference [MD]: 4.45%, 95%CI: -3.04, 11.93, p=0.244; Q=2.18, I(2)=0%). In meta-regression, changes in plasma adiponectin concentrations following vitamin D supplementation were found to be independent of treatment duration (slope: 0.25; 95%CI: -0.69, 1.19; p=0.603) and changes in serum 25-hydroxy vitamin D [25(OH)D] levels (slope: -0.02; 95%CI: -0.15, 0.12; p=0.780). Meta-analysis of data from 6 studies did not find a significant change in plasma leptin concentrations following vitamin D supplementation (MD: -4.51%, 95%CI: -25.13, 16.11, p=0.668; Q=6.41, I(2)=21.97%). Sensitivity analysis showed that this effect size is sensitive to one of the studies; removing it resulted in a significant reduction in plasma leptin levels (MD: -12.81%, 95%CI: -24.33, -1.30, p=0.029). In meta-regression, changes in plasma leptin concentrations following vitamin D supplementation were found to be independent of treatment duration (slope: -1.93; 95%CI: -4.08, 0.23; p=0.080). However, changes in serum 25(OH)D were found to be significantly associated with changes in plasma leptin levels following vitamin D supplementation (slope: 1.05; 95%CI: 0.08, 2.02; p=0.033). In conclusion, current data did not indicate a significant effect of vitamin D supplementation on adiponectin and leptin levels.